2022
DOI: 10.3174/ajnr.a7646
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Thalamus, Hippocampus, and Brainstem in Hypsarrhythmia of West Syndrome: Simultaneous Recordings of Electroencephalography and fMRI Study

Abstract: BACKGROUND AND PURPOSE: West syndrome is a developmental and epileptic encephalopathy characterized by epileptic spasms, neurodevelopmental regression, and a specific EEG pattern called hypsarrhythmia. Our aim was to investigate the brain activities related to hypsarrhythmia at onset and focal epileptiform discharges in the remote period in children with West syndrome using simultaneous electroencephalography and fMRI recordings.MATERIALS AND METHODS: Fourteen children with West syndrome underwent simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Assessment of hemodynamic responses by simultaneous EEG and functional magnetic resonance imaging (fMRI) has revealed that high-voltage slow waves are produced from subcortical structures including the thalamus, hippocampus, and brainstem nuclei [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of hemodynamic responses by simultaneous EEG and functional magnetic resonance imaging (fMRI) has revealed that high-voltage slow waves are produced from subcortical structures including the thalamus, hippocampus, and brainstem nuclei [ 13 ].…”
Section: Introductionmentioning
confidence: 99%